การประยุกต์ใช้เครื่องบินบังคับอัตโนมัติ เพื่อสร้างฐานข้อมูลแบบจำลองสารสนเทศอาคารสำหรับงานสถาปัตยกรรมผังเมือง กรณีศึกษา อ.ธาตุพนม จ.นครพนม - บุญเหลือ ธราวุฒิ (Asian Creative Architecture, Art and Design, 2018)
Abstract This paper presents the applying of Drone for generating a geography information on Building Information Modeling (BIM) for the area of urban architecture. This geography information can be used for developing better environment for example building information, coverage/land use and ground imagery. This geography information can be drawn from many sources or can be used to create model builder Autodesk Infraworks program. However, such geography information is not up to date, and cannot demonstrate all detail of the existing area; therefore, there is the limitation for site analysis and urban design process. Applying Drone for generated building information modeling (BIM) for urban architecture can be a useful methodology for urban designer and related fields. It can be used for analysis an area for urban design process, and can be use to understand urban context and surrounding in three dimension. Moreover, it can apply the aerial photography to add data source as a base map, which have very high resolution and up to date. This paper explains the process to create an aerial photography by Drone, and using related programs, technique as well as all equipment that can be the method for analysis an urban planning. The outcome of aerial photography covers the area approximately 1 sq.km., which can be used as the data sources on Autodesk Infraworks program under the concept of Building Information Modeling (BIM). This paper uses the case study of Wat Phra Tat Phanom Woramahawihan and surrounding areas of that Phanom District, Nakhon Phanom Province as the geography information for the case study area. Keywords: Drone, Aerial Photography, Building Information Modeling, Urban Architecture